2017
DOI: 10.1111/cea.12940
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that eating baked egg or milk influences egg or milk allergy resolution: a systematic review

Abstract: There is little evidence to address the hypothesis that the ingestion of baked hen's egg or cow's milk results in more patients outgrowing their hen's egg or cow's milk allergy respectively. Data are required from a trial comparing the resolution rates of baked-tolerant participants who are randomized to ingest or avoid baked products to assess the accuracy of this hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 39 publications
1
35
0
2
Order By: Relevance
“…Each biscuit contains between 23 and 43 mg of milk protein and in the first dose our patients ingested about 0.35 mg of milk protein. This is much lower than standardized baked milk challenge protocols where patients ingested a muffin containing a total dose equivalent of 1.3 g of milk protein, or the lower dose of 0.8 g . All of these studies report patients experiencing anaphylactic reactions requiring treatment with epinephrine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each biscuit contains between 23 and 43 mg of milk protein and in the first dose our patients ingested about 0.35 mg of milk protein. This is much lower than standardized baked milk challenge protocols where patients ingested a muffin containing a total dose equivalent of 1.3 g of milk protein, or the lower dose of 0.8 g . All of these studies report patients experiencing anaphylactic reactions requiring treatment with epinephrine.…”
Section: Discussionmentioning
confidence: 99%
“…The timing and evolution of developing tolerance cannot be effectively predicted by clinical features or biological markers, so is determined by the clinical response to milk reintroduction. Tolerance to extensively heated milk (referred to as “baked milk”) develops earlier than to fresh pasteurized milk, and early regular dietary incorporation of baked milk may furthermore accelerate the natural resolution of CMA . In addition, the ability to incorporate baked milk liberalizes the diet and thereby may not only improve the quality of life by reducing anxiety over accidental ingestion and improve nutrition but also reduce the severity of allergic reactions on further milk contact .…”
Section: Introductionmentioning
confidence: 99%
“…6 Moreover, the ability of OIT to induce long-term food tolerance and the adverse effects, especially gastroenteric complications, are yet to be established. 7,13 It has been reported that many children with milk allergy can better tolerate the modified allergens in baked milk products. 14 Some studies have sought to assess the efficacy of baked milk products in accelerating tolerance to unheated milk.…”
Section: Discussionmentioning
confidence: 99%
“…40 Unfortunately, there seems to be limit evidence to suggest that this approach speeds up outgrowth although it may simplify meals times for families. 41 A potential treatment strategy is omalizumab, and Vetander and colleagues publish data to suggest that an individualized dosing can prevent reactions in patients with food allergy. 42 Specific immunotherapy is another option although serious adverse events are not infrequent.…”
Section: Food Allergymentioning
confidence: 99%